NH3 release during the snow evaporation process in typical cities in Northeast China - Xiaoteng Liu; Hongsheng Jia; Yunze Zhao; Yachao Zhang; Haodong Hou; Yingying Xu (Scientific Reports)
Abstract NH3 is the most important alkaline gas in the atmosphere and functions as a precursor to secondary ammonium salts. Therefore, identifying its sources and quantifying its emissions is imperative. NH4 + represents a principal component of atmospheric particulate pollutants. As particulate matter acts as a condensation nucleus for wet deposition, the NH4 + concentrations in precipitation are typically elevated. During the evaporation process of wet deposition, NH4 + is likely to be re-emitted as a gas (NH3). In Northeast China, heavy and frequent snowfall occurs, making it crucial to elucidate the NH3 release flux and the factors influencing this release during the snow evaporation process in representative cities of this region. This study collected snow samples from five notable snowfall events in Changchun, Jilin Province that occurred from November 2023 to March 2024, to conduct indoor simulated evaporation experiments (among them, the actual phase changes of two snowfall events consisted mainly of evaporation, whereas those of the other three events consisted mainly of sublimation). The results indicated that during the snow evaporation process, the average ratio (R) of NH4 + re-emitted as NH3 was 39.28 ± 12.07%. The average release flux (F) was 1624.58 ± 2064.5 μg/m2, and the average release rate (V) was 361.33 ± 465.31 ng/(m2·s). Within the 100-m atmospheric boundary layer, the total NH3 flux that was released subsequently during the evaporation of all snowfall events in Changchun during the study period was 46.97 mg/m2. The average release flux for individual snowfall events was 688.66 μg/m2, which constituted approximately 2.44% of the NH3 concentration documented in the winter atmosphere of Changchun. During the snow evaporation or sublimation process, R was positively correlated with the environmental temperature (P < 0.05) and negatively correlated with both the environmental wind speed and snowfall amount (P < 0.05). Significant variations in R were observed across multiple functional areas, which were ranked in descending order as follows: commercial areas (R = 26.16%), residential areas (R = 22.01%), cultural and educational areas (R = 20.7%), and industrial areas (R = 18.01%). The influence of a snow-melting agent (NaCl) on the conversion rate of NH3 initially increased but then subsequently decreased as the dose increased. The lowest measured value (R = 22.02%) was 0 mg/L, whereas the peak measured value (R = 30.31%) was attained at a concentration of 200 mg/L. The findings of this research are important for illuminating the cycling process of NH3 in the atmosphere and for the comprehensive management of air quality.